2009
DOI: 10.1197/jamia.m3119
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Screening Improves Efficiency in Clinical Trial Recruitment

Abstract: This study evaluated the performance of an electronic screening (E-screening) method and used it to recruit patients for the NIH sponsored ACCORD trial. Out of the 193 E-screened patients, 125 met the age criterion ("age>or=40"). For all of these 125 patients, the performance of E-screening was compared with investigator review. E-screening achieved a negative predictive accuracy of 100% (95% CI: 98-100%), a positive predictive accuracy of 13% (95% CI: 6-13%), a sensitivity of 100% (95% CI: 45-100%), and a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 3 publications
1
95
0
Order By: Relevance
“…Authors in one study compared an e-screening strategy with investigator review for recruitment into a clinical trial with a low prevalence of eligible patients. 36 The e-screening approach showed an over fivefold improvement on the investigator review approach (13% compared to 2.4% PPV). …”
Section: Discussionmentioning
confidence: 98%
“…Authors in one study compared an e-screening strategy with investigator review for recruitment into a clinical trial with a low prevalence of eligible patients. 36 The e-screening approach showed an over fivefold improvement on the investigator review approach (13% compared to 2.4% PPV). …”
Section: Discussionmentioning
confidence: 98%
“…Study 7 did apply the system from the beginning of the study; therefore, there is no comparison to previous values. [16] reported recently about improved efficiency in clinical trial recruitment using electronic screening. We conducted a PubMed query (MeSH terms 'patient selection' and 'hospital information systems', manual review of search results) and found relatively few reports of clinical trial alert systems, mainly in the outpatient setting.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all CTRSS “perform ‘pre-screening’ for clinical research staff” [115] instead of trying to determine the actual eligibility of a patient. They do not replace manual chart review, but act as a filter that limits the number of patients who require such by selecting the most likely candidates.…”
Section: Resultsmentioning
confidence: 99%